Solid state bioconversion of oil palm empty fruit bunches for cellulase enzyme production using a rotary drum bioreactor - Alam, Md. Zahangir; Al-Mamun, Abdullah; Qudsieh, Isam Y.; Muyibi, Suleyman Aremu; Mohd. Salleh, Hamzah; Omar, Nor Marina (Elsevier Science, 2009)
Bioconversion of oil palm lignocellulosic biomass in the form of empty fruit bunches (EFB) as the major substrate into cellulase enzyme was studied in the laboratory. A fungal strain, Trichoderma harzianum T2008 was used to evaluate the solid state bioconversion of EFB for cellulase production. The study was conducted in two systems: an Erlenmeyer flask (EF, 500 mL) and a horizontal rotary drum bioreactor (RDB, 50 L), designed and fabricated locally. The highest cellulase activity on the fourth day of fermentation in the EF was 8.2 filter paper activity (FPA)/gram dry solids (gds) of EFB, while its activity from the RDB was 10.1 FPA/gds on the second day of fermentation. Glucosamine, reducing sugar and pH were also determined to evaluate the substrate uptake and growth conditions during the entire fermentation period.